Biological Performance of Phosalone and Malathion in Grapes (Vitis vinifera L. cv Anab-e-shahi) - Reddy, C. Narendra; Reddy, D. Jagdishwar; Reddy, K. Narsimha (International Journal of Bio-resource and Stress Management, 2011)
The experiment was conducted during February-March, 2006 with grape variety Anab-e-shahi. Two sprays of malathion (0.05%) and phosalone (0.07%) were applied with first spray at berry formation stage and second spray at 15 days after first spray. The dissipation pattern of malathion revealed that initial deposit of malathion 1.24 mg kg-1 was dissipated to 0.01 mg kg-1 on 15 days after second spray when malathion (0.05%) was sprayed twice at berry formation stage. The dissipation pattern of phosalone revealed that the initial deposit of phosalone 0.33 mg kg-1 was dissipated to 0.01 mg kg-1 on 10 days after second spray when phosalone (0.07%) was sprayed twice at berry formation stage. The maximum residue limit for malathion and phosalone is 8 and 5 mg kg -1, respectively. The initial deposits of malathion and phosalone were below maximum residue limits. The waiting period for safe harvest of grape berries after two spray of malathion (0.05%) and phosalone (0.07%) when given at berry formation stage is one day.